Zentralamerika: Bericht über eine Forschungsreise 1953/54 - Lauer, Wilhelm (ERDKUNDE, 1954)
Following an invitation from the Instituto Tropical de Investigaciones Científicas in San Salvador, El Salvador, the author spent the period 7 March 1953 to 14 February 1954 on a scientific expedition through Central America. Geographical research in this area must on the whole take its starting point from the work of Karl Sapper, who between 1888 and 1900 travelled in almost all Central American states. Topographical maps have begun to appear only recently, issued by the newly established cartographic institutes in El Salvador and Costa Rica, but the U. S. American Canal Zone of Panamá is the only area for which a complete set of maps is available. Dr. Lauer studied problems of climate and its bearing on vegetation, and further, problems of economic geography. Investigations were aimed in particular at the study of edaphically determined types of vegetation in the different climatic regions and altitudinal zones. Problems in economic geography are largely connected with the widespread growth of coffee and its production. In El Salvador, the most progressive in its economy of all the Central American states, detailed type studies were made in different economic regions. The pronounced contrast between the permanently humid Atlantic and the intermittently humid Pacific sides of Central America emerges clearly in all economic geographical phenomena.